Producing Eucalyptus pellita wood polyol through liquefaction forpolyurethane film production - Abd Hilmi, Nurul Hazwani; Lodin, Valeritta; Gilbert Jesuet, Melissa Sharmah; Salim, Sabiha; Seng, Hua Lee; Hori, Naruhito; Takemura, Akio; Palle, Ismawati (Elsevier, 2023)
Depending on the reaction conditions, liquefaction of woody biomass produces a variety of polyol properties. The liquefaction of Eucalyptus pellita (EP) wood powder was studied to optimize the liquefaction conditions for maximum yield. The solvent ratio (PEG/glycerol: 0–25), temperature (140–170 ℃), time (120–150 min) and sulfuric acid as catalyst (1–4) were varied. The hydroxyl amount (OHA), acid value (AV), and molecular weight (Mw) of the resulting polyol were determined. To study the chemical components and thermal characteristics of resulting polyol, infrared spectra of Fourier transform infrared spectroscopy (FT-IR) and thermogravimetric test (TGT) were used. The bio-polyol produced under optimal reaction conditions was then blend with pMDI at different ratio of NCO/OH to prepare E. pellita polyurethane (EPPU) films. Performance of the EPPU film was evaluated by tensile test. The optimum liquefaction reaction conditions resulted in 89.2 EP liquefied wood when the amount of H2SO4 (catalyst) was 3 in a PEG/G (80/20) solvent mixture at 160 ℃ for 150 min. A thorough examination of the liquefied properties reveals that using up to 20 glycerol as a co-solvent is effective in speeding up the liquefaction process, follow-on in high wood conversion with OHA and AV of about 337 mg KOH/g and 3.9 mg KOH/g, respectively. Tensile value improved while elongation at break decreased as the NCO/OH ratios for EPPU film properties increased. The EPPU film obtained at NCO/OH of 2.8 had the highest tensile strength and maximum elongation, at 45.8 MPa and 12.6, respectively.